The Impact of Value-Based Leadership on Teacher Commitment and Job Performance in Private Islamic Senior High - Nurdelima Waruwu; Ahmad Kultur Hia; Alex Winarno; Deni Hermana; Ran Liu (Journal of Leadership in Organizations, 2023)
Introduction/Main Objectives: This study aims to analyze the impact of authentic leadership on teacher performance in private Islamic senior high schools (ISHS) mediated by commitment. Background Problems: Authentic leadership as a value-based approach offers solutions to teacher performance, but there are complexities and doubts that require further exploration and empirical testing. Novelty: It provides an in-depth exploration of the role of authentic leadership in promoting commitment and performance. It consolidates existing knowledge and synthesizes relevant value-based leadership (VBL) and authentic leadership (AL) theories. It provides a valuable resource for further research and practical applications in this educational setting. Research Methods: This study applied an explanatory survey by using a set of questionnaires. The respondents consisted of teachers and administrative staff. This study successfully collected the data of 462 respondents randomly chosen. Finding/Results: The interaction between leaders and subordinates is a dynamic process that directly influences performance and organizational commitment. A leader's ethical, moral, and values guide their actions and interactions with followers, ultimately fostering commitment and driving performance. Conclusion: Authentic leadership not only directly influences commitment and performance but also indirectly affects performance by nurturing a strong sense of commitment among teachers. Research implications: AL's cultivated values act as a beacon for nurturing commitment and performance. Practical implications underscore the paramount role of values in authentic leadership to ensure and focus on strategies for cultivating authentic leadership values to pave the way for enhancing teacher commitment and performance.